2011
DOI: 10.1037/a0025150
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of cerebellar-dependent associative learning in schizophrenia: Effects of varying and shifting interstimulus interval on eyeblink conditioning.

Abstract: Eyeblink conditioning abnormalities have been reported in schizophrenia, but the extent to which these anomalies are evident across a range of delay intervals (i.e., ISI intervals) is unknown. In addition, the effects of interstimulus interval (ISI) shifts on learning are unknown, though such manipulations can be informative about the plasticity of cerebellar timing functions. Therefore, the primary purpose of the present study was to investigate the interactions between interstimulus interval (ISI) manipulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 55 publications
2
19
1
Order By: Relevance
“…Eyeblink conditioning is significantly impaired in the patients, and they exhibit significantly fewer CRs during the latter two phases of acquisition than controls. These data replicate previous studies reporting abnormalities in eyeblink conditioning in schizophrenia patients (Brown et al, 2005; Bolbecker et al, 2009, 2011). However, the onset timing of both the overall eyeblink and the CR was non-significant (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Eyeblink conditioning is significantly impaired in the patients, and they exhibit significantly fewer CRs during the latter two phases of acquisition than controls. These data replicate previous studies reporting abnormalities in eyeblink conditioning in schizophrenia patients (Brown et al, 2005; Bolbecker et al, 2009, 2011). However, the onset timing of both the overall eyeblink and the CR was non-significant (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Early work examining eyeblink conditioning in schizophrenia using behavioral measures has suggested that patients condition faster than controls and have a higher percentage of CRs (Spain, 1966; Sears et al, 2000). However, more recent studies have reported the opposite result (Hofer et al, 2001; Brown et al, 2005; Edwards et al, 2008; Bolbecker et al, 2009, 2011) indicating eyeblink conditioning deficits in schizophrenia.…”
Section: Introductionmentioning
confidence: 90%
“…Compared to controls, patients with schizophrenia showed fewer CR incidences and longer CR onset latencies while shifting of the interstimulus interval did not influence CR rates in both groups [190].…”
Section: Marcus Gerwigmentioning
confidence: 73%
“…Since the medial prefrontal cortex has been implicated in the pathophysiology of schizophrenia(20), the top-down regulation to motor regions may play a role in motor circuitry abnormalities in schizophrenia. Besides the prefrontal–motor circuitry, other motor circuitries such as the cerebello-thalamo-motor circuit may also be relevant as it controls motor learning and postural control(21,22). Furthermore, altered sensorimotor and basal ganglia circuit abnormalities and their related motor behavioral problems have also been shown in schizophrenia(2327).…”
Section: Introductionmentioning
confidence: 99%